Genetic evaluation of multibreed populations of milking bovines - Hernández, Arelis; Ponce de León, Raquel; García, Sonia María (Cuban Journal of Agricultural Science, 2016)
In order to fulfill this study, a total of 130,111 records of accumulatedmilk production, up to 305 days (L305), from three Cuban geneticenterprises and between 1984 and 2013, were used. Out of a totalof 61,471 cows, 12,496 belonged to Mambí de Cuba breed (3/4Holstein ¼ Zebu), 17,178 Siboney de Cuba breed (5/8 Holstein 3/8Zebu) and 31,797 Holstein. The purpose of the study was to comparethe multibreed genetic evaluation for milk production with geneticevaluations of each breed. To estimate the genetic indicators andbreeding values of L305, a univariate animal model was used, whichincluded, as fixed effects, the combination herd-year-four-monthperiod of parturition. The age at parturition was used as linear andsquare covariable, random effects of the animal, the effect of theenvironment and residues. Breed was also included as fixed effect inthe multibreeding genetic evaluation. Heritabilities and repetitions were 0.31 ± 0.01 y 0.40 ± 0.01 for the multibreeding genetic evaluation, and 0.18 ± 0.05 and 0.41±0.02, 0.14± 0.05 and 0.41 ± 0.02, 0.12 ± 0.01 and 0.25 ± 0.01 for the independent racial evaluations of Mambí de Cuba, Siboney de Cuba and Holstein, respectively. In the multibreeding genetic evaluation, the estimation of heritability and the accuracy of breeding values for milk production of the three studied breeds increased regarding the evaluations of each individual breed, mainly because of a higher amount of information and higher connectivity among breeds, which contribute to decrease the environmental variance. It can be concluded that the inclusion of multibreeding genetic evaluations on the program of genetic improvement of Cuban milking bovines allows to obtain a better accuracy of breeding values, which will also contribute to the increase of the genetic progress for milk production.Key words: genetic evaluation, multibreed, crossing